PERAN GURU DALAM PENGUATAN KARAKTER SISWA DI ERA SOCIETY 5.0 (OPTIMALISASI PEMANFAATAN TEKNOLOGI PEMBELAJARAN) - Zaki, Ammar; Hidayat, Tita Nurmalinasari; Furqan, M. Hafizul; Saifuddin, Saifuddin; Winarty, Asih (Jurnal Dedikasi Pendidikan, 2024)
The era of society 5.0 is a concept where people already understand and understand the importance of the role of Information and Communication Technology so that people will get a positive impact from the development of technology. In the world of education in the era of society 5.0, students are required to have some expertise in technology which is supported by the ability to think creatively, innovatively, critically, communication skills and collaboration skills. In addition to students who must have various skills, teachers as educators have their own role, namely helping students in facing the era of society 5.0. One of the roles of teachers is to provide character education to students to form good ethics so that these characters can make students able to collaborate with technology positively. The purpose of this study is to explain the importance of the role of teachers in strengthening student character, especially in the era of society 5.0. In addition, the purpose of this study is to explain how important teachers are in optimizing the use of learning technology to help students face the era of society 5.0. The method used is a Qualitative Approach with a case study research method. The result of this study is that a teacher has an important role in strengthening student character in the era of society 5.0. by doing character education at school. Character education can be done by optimizing the use of technology in learning